Development of logical thinking in the acquisition of the concept of number from psychomotor skills (Revista horizonte, 2011)
The acquisition of the concept of number is a fundamental prerequisite for the development of logical thinking. This article presents the results of the study of the acquisition of the concept of number, based on the psychomotor skills, where they compare initial and finishes tests conducted with two groups (A and B) of children in transition of the Republic school Argentina in the municipality of Puerto Montt (Chile), to determine the effectiveness of the education program psychomotor proposed to group Abased on the concepts that make up the concept of number, in the class of physical education, compared to group B with traditional physical education program is developed